A humanized mouse identifies the bone marrow as a niche with low therapeutic IgG activity - Lux, Anja; Seeling, Michaela; Baerenwaldt, Anne; Lehmann, Birgit; Schwab, Inessa; Repp, Roland; Meidenbauer, Norbert; Mackensen, Andreas; Hartmann, Arndt; Heidkamp, Gordon Frederik; Dudziak, Diana; Nimmerjahn, Falk (Cell Reports, 2014)
Genetic differences between humans and in vivo model systems, including mice and nonhuman primates, make it difficult to predict the efficacy of immunoglobulin G (IgG) activity in humans and understand the molecular and cellular mechanisms underlying that activity. To bridge this gap, we established a small-animal model system that allowed us to study human IgG effector functions in the context of an intact human immune system without the interference of murine Fc? receptors expressed on mouse innate immune effector cells in vivo. Using a model of B cell depletion with different human IgG variants that recognize CD20, we show that this humanized mouse model can provide unique insights into the mechanism of human IgG activity in vivo. Importantly, these studies identify the bone marrow as a niche with low therapeutic IgG activity.
EVALuna2:6588

A Monosaccharide Residue Is Sufficient to Maintain Mouse and Human IgG Subclass Activity and Directs IgG Effector Functions to Cellular Fc Receptors. - Kao, Daniela; Danzer, Heike; Collin, Mattias; Groß, Andrea; Eichler, Jutta; Stambuk, Jerko; Lauc, Gordan; Lux, Anja; Nimmerjahn, Falk (Cell Reports, 2015)
Immunoglobulin G (IgG) glycosylation modulates antibody activity and represents a major source of heterogeneity within antibody preparations. Depending on their glycosylation pattern, individual IgG glycovariants present in recombinant antibody preparations may trigger effects ranging from enhanced pro-inflammatory activity to increased anti-inflammatory activity. In contrast, reduction of IgG glycosylation beyond the central mannose core is generally believed to result in impaired IgG activity. However, this study reveals that a mono- or disaccharide structure consisting of one N-acetylglucosamine with or without a branching fucose residue is sufficient to retain the activity of the most active human and mouse IgG subclasses in vivo and further directs antibody activity to cellular Fcγ receptors. Notably, the activity of minimally glycosylated antibodies is not predicted by in vitro assays based on a monomeric antibody-Fcγ-receptor interaction analysis, whereas in vitro assay systems using immune complexes are more suitable to predict IgG activity in vivo.

An industrial-grade Nicotiana benthamiana line for the production of glycoproteins carrying fucose-free galactosylated N-glycans - Kogelmann, Benjamin; Melnik, Stanislav; Keshvari, Tahereh; Bogner, Michaela; Lavoie, Pierre Olivier; D`Aoust, Marc Andre; Hermle, Antonia; Lux, Anja; Strasser, Richard; Stöger, Eva; Steinkellner, Herta (New Biotechnology, 2025)
β1,4-galactosylation is a typical human N-glycan formation with functional impact on proteins, particularly known for IgGs. Therefore, the expression of recombinant proteins with controlled galactosylation is an important quality parameter in the biotech industry. Here we describe the establishment of a plant-based expression platform for the manufacturing of recombinant proteins carrying β1,4-galactosylated N-glycans. A genome-edited Nicotiana benthamiana glycosylation mutant (NbXF-KO) that synthesizes conserved eukaryotic GnGn structures served as a template for further elongation toward β1,4-galactosylated N-glycans. A hybrid β1,4-galactosyltransferase gene that targets the enzyme to a post-Golgi compartment was introduced into the NbXF-KO genome without any additional foreign DNA sequence. The efficient generation of “marker-free” transgenic lines (NbXF-KOGal) was achieved by using a dual-vector strategy and visual screening procedures. Of note, a monoclonal antibody expressed in NbXF-KOGal exhibited up to 70 % galactosylated, fucose/xylose-free N-glycans, in a batch-to-batch consistent manner. Given recent findings attributing anti-inflammatory activities to nonfucosylated, galactosylated IgG, our results gain new significance.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Galactosylated fucose-free N-glycans; N-glycan engineering; Nicotiana benthamiana; Recombinant glycoproteins; β1; 4-galactosylation

Antibodies and complement are key drivers of thrombosis - Stark, Konstantin; Kilani, Badr; Stockhausen, Sven; Busse, Johanna; Schubert, Irene; Tran, Thuy Duong; Gaertner, Florian; Leunig, Alexander; Pekayvaz, Kami; Nicolai, Leo; Fumagalli, Valeria; Stermann, Julia; et al. (Immunity, 2024)
Venous thromboembolism (VTE) is a common, deadly disease with an increasing incidence despite preventive efforts. Clinical observations have associated elevated antibody concentrations or antibody-based therapies with thrombotic events. However, how antibodies contribute to thrombosis is unknown. Here, we show that reduced blood flow enabled immunoglobulin M (IgM) to bind to FcμR and the polymeric immunoglobulin receptor (pIgR), initiating endothelial activation and platelet recruitment. Subsequently, the procoagulant surface of activated platelets accommodated antigen- and FcγR-independent IgG deposition. This leads to classical complement activation, setting in motion a prothrombotic vicious circle. Key elements of this mechanism were present in humans in the setting of venous stasis as well as in the dysregulated immunothrombosis of COVID-19. This antibody-driven thrombosis can be prevented by pharmacologically targeting complement. Hence, our results uncover antibodies as previously unrecognized central regulators of thrombosis. These findings carry relevance for therapeutic application of antibodies and open innovative avenues to target thrombosis without compromising hemostasis.
CRIS-Team Scopus Importer:2024-11-08
Keywords: antibodies; complement; COVID-19; endothelial cells; Fc-receptors; neutrophil extracellular traps; neutrophils; platelets; thrombosis; venous thromboembolism

B-cell modulation with anti-CD79b antibodies ameliorates experimental autoimmune encephalitis in mice - Renner, Kerstin; Neumayer, Sophia; Talke, Yvonne; Buchtler, Simone; Schmidbauer, Kathrin; Nimmerjahn, Falk; Lux, Anja; Winter, Frederike; Salewski, Jan-Nicklas; Mack, Matthias (European Journal of Immunology, 2022)
B cells play a major role in the pathogenesis of many autoimmune diseases like MS, rheumatoid arthritis, or systemic lupus erythematosus. Depletion of B cells with anti-CD20 antibodies is an established therapy for MS. However, total B-cell depletion will also affect regulatory B cells that are known to suppress autoimmune responses. In our studies, we describe an alternative approach based on targeting CD79b that induces only partial B-cell depletion and achieves therapeutic effects by B-cell modulation. Prophylactic and therapeutic treatment with an antibody against CD79b and also a deglycosylated variant of this antibody, lacking effector function like antibody-dependent cellular cytotoxicity or complement activation, significantly reduced the development and progression of EAE in mice. Our data show that modulation of B cells via CD79b is equally effective as almost complete B-cell depletion with anti-CD20 antibodies and may constitute an alternative approach to treat MS.
CRIS-Team WoS Importer:2022-01-21

Bone- and cartilage-protective effects of a monoclonal antibody against colony-stimulating factor 1 receptor in experimental arthritis - Toh, Myew-Ling; Bonnefoy, Jean-Yves; Accart, Nathalie; Cochin, Sandrine; Pohle, Sandy; Haegel, Helene; De Meyer, Micael; Zemmour, Christophe; Preville, Xavier; Guillen, Christine; Thioudellet, Christine; Ancian, Philippe; et al. (Arthritis and Rheumatology, 2014)
Colony-stimulating factor 1 receptor (CSF-1R) essentially modulates monocyte proliferation, migration, and activation, which are considered important for the pathogenesis of rheumatoid arthritis (RA). We undertook this study to determine CSF-1R expression in human RA as well as the efficacy of a specific anti-CSF-1R monoclonal antibody (AFS98) in 2 different animal models of RA.CSF-1R expression was examined in blood, synovium, and bone samples from RA patients, osteoarthritis (OA) patients, and healthy subjects. The efficacy of AFS98 was examined by clinical assessment, histology, and bone histomorphometry in collagen-induced arthritis (CIA) and serum-transfer arthritis.CSF-1R expression was increased in the synovium of RA patients compared to OA patients and healthy controls in fibroblast-like synoviocytes, follicular dendritic cells, macrophages, and osteoclasts. Circulating RA monocytes and neutrophils but not lymphocytes were CSF-1R+. In mice, blockade of CSF-1R abrogated cartilage damage, bone erosion, and systemic bone loss, and this was associated with the depletion of osteoclasts in both models. While blockade of CSF-1R did not affect inflammation in passive serum-transfer arthritis, it significantly reduced inflammation in CIA, and this was associated with the absence of synovial macrophages and reduced splenic CD11b+Gr-1- monocytes.CSF-1R was broadly expressed in human RA. Blockade of CSF-1R protected against bone and cartilage destruction in both mouse models and also showed significant antiinflammatory effects in the CIA model. These data provide evidence for CSF-1R as a therapeutic target in RA.
EVALuna2:12982

Complement-Dependent Activity of CD20-Specific IgG Correlates With Bivalent Antigen Binding and C1q Binding Strength - Bondza, Sina; Marosán, Anita; Kara, Sibel; Lösing, Josephine; Peipp, Matthias; Nimmerjahn, Falk; Buijs, Jos; Lux, Anja (Frontiers in Immunology, 2021)
Monoclonal antibodies directed against the CD20 surface antigen on B cells are widely used in the therapy of B cell malignancies. Upon administration, the antibodies bind to CD20 expressing B cells and induce their depletion via cell- and complement-dependent cytotoxicity or by induction of direct cell killing. The three antibodies currently most often used in the clinic are Rituximab (RTX), Ofatumumab (OFA) and Obinutuzumab (OBI). Even though these antibodies are all of the human IgG1 subclass, they have previously been described to vary considerably in the effector functions involved in therapeutic B cell depletion, especially in regards to complement activation. Whereas OFA is known to strongly induce complement-dependent cytotoxicity, OBI is described to be far less efficient. In contrast, the role of complement in RTX-induced B cell depletion is still under debate. Some of this dissent might come from the use of different in vitro systems for characterization of antibody effector functions. We therefore set out to systematically compare antibody as well as C1q binding and complement-activation by RTX, OFA and OBI on human B cell lines that differ in expression levels of CD20 and complement-regulatory proteins as well as human primary B cells. Applying real-time interaction analysis, we show that the overall strength of C1q binding to live target cells coated with antibodies positively correlated with the degree of bivalent binding for the antibodies to CD20. Kinetic analysis revealed that C1q exhibits two binding modes with distinct affinities and binding stabilities, with exact numbers varying both between antibodies and cell lines. Furthermore, complement-dependent cell killing by RTX and OBI was highly cell-line dependent, whereas the superior complement-dependent cytotoxicity by OFA was independent of the target B cells. All three antibodies were able to initiate deposition of C3b on the B cell surface, although to varying extent. This suggests that complement activation occurs but might not necessarily lead to induction of complement-dependent cytotoxicity. This activation could, however, initiate complement-dependent phagocytosis as an alternative mechanism of therapeutic B cell depletion.
CRIS-Team Scopus Importer:2021-02-05
Keywords: B cells; C1q; CD20; CDC; interaction; Obinutuzumab; Ofatumumab; Rituximab

Detection of experimental and clinical immune complexes by measuring SHIP-1 recruitment to the inhibitory FcγRIIB - Stopforth, Richard J.; Oldham, Robert J.; Tutt, Alison L.; Duriez, Patrick; Chan, H. T. Claude; Binkowski, Brock F.; Zimprich, Chad; Li, Dun; Hargreaves, Philip G.; Cong, Mei; Reddy, Venkat; Leandro, Maria J.; et al. (Journal of Immunology, 2018)
Fc γ receptors (FcγR) are involved in multiple aspects of immune cell regulation, are central to the success of mAb therapeutics, and underpin the pathology of several autoimmune diseases. However, reliable assays capable of accurately measuring FcγR interactions with their physiological ligands, IgG immune complexes (IC), are limited. A method to study and detect IC interactions with FcγRs was therefore developed. This method, designed to model the signaling pathway of the inhibitory FcγRIIB (CD32B), used NanoLuc Binary Interaction Technology to measure recruitment of the Src homology 2 domain-containing inositol phosphatase 1 to the ITIM of this receptor. Such recruitment required prior cross-linking of an ITAM-containing activatory receptor, and evoked luciferase activity in discrete clusters at the cell surface, recapitulating the known biology of CD32B signaling. The assay detected varying forms of experimental IC, including heat-aggregated IgG, rituximab-anti-idiotype complexes, and anti-trinitrophenol-trinitrophenol complexes in a sensitive manner (≤1 μg/ml), and discriminated between complexes of varying size and isotype. Proof-of-concept for the detection of circulating ICs in autoimmune disease was provided, as responses to sera from patients with systemic lupus erythematosus and rheumatoid arthritis were detected in small pilot studies. Finally, the method was translated to a stable cell line system. In conclusion, a rapid and robust method for the detection of IC was developed, which has numerous potential applications including the monitoring of IC in autoimmune diseases and the study of underlying FcγR biology.
CRIS-Team Scopus Importer:2022-09-23

Dissecting FcγR Regulation through a Multivalent Binding Model - Robinett, Ryan A.; Guan, Ning; Lux, Anja; Biburger, Markus; Nimmerjahn, Falk; Meyer, Aaron S. (Cell Systems, 2018)
Many immune receptors transduce activation across the plasma membrane through their clustering. With Fcγ receptors (FcγRs), this clustering is driven by binding to antibodies of differing affinities that are in turn bound to multivalent antigen. As a consequence of this activation mechanism, accounting for and rationally manipulating immunoglobulin (Ig)G effector function is complicated by, among other factors, differing affinities between FcγR species and changes in the valency of antigen binding. In this study, we show that a model of multivalent receptor-ligand binding can effectively account for the contribution of IgG-FcγR affinity and immune complex valency. This model in turn enables us to make specific predictions about the effect of immune complexes of defined composition. In total, these results enable both rational immune complex design for a desired IgG effector function and the deconvolution of effector function by immune complexes. Robinett et al. show that a multivalent binding model can predict antibody binding to immune effector cells. By using this model with measurements of the FcγR combinations expressed across effector populations, they are able to predict the outcome of tumor-targeted antibodies and identify the essential innate cell types. These results inform the further rational design of therapeutic antibodies and potentially antibody combinations.
CRIS-Team Scopus Importer:2022-09-23
Keywords: antibodies; cell specificity; effector function; FcγR receptors; immunology

Dissection of complement and Fc-receptor-mediated pathomechanisms of autoantibodies to myelin oligodendrocyte glycoprotein - Mader, Simone; Ho, Samantha; Wong, Hoi Kiu; Baier, Selia; Winklmeier, Stephan; Riemer, Carolina; Rübsamen, Heike; Fernandez, Iris Marti; Gerhards, Ramona; Du, Cuilian; Chuquisana, Omar; Lünemann, Jan D.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Autoantibodies against myelin oligodendrocyte glycoprotein (MOG) have recently been established to define a new disease entity, MOG-antibody-associated disease (MOGAD), which is clinically overlapping with multiple sclerosis. MOG-specific antibodies (Abs) from patients are pathogenic, but the precise effector mechanisms are currently still unknown and no therapy is approved for MOGAD. Here, we determined the contributions of complement and Fc-receptor (FcR)-mediated effects in the pathogenicity of MOG-Abs. Starting from a recombinant anti-MOG (mAb) with human IgG1 Fc, we established MOG-specific mutant mAbs with differential FcR and C1q binding. We then applied selected mutants of this MOG-mAb in two animal models of experimental autoimmune encephalomyelitis. First, we found MOG-mAb-induced demyelination was mediated by both complement and FcRs about equally. Second, we found that MOG-Abs enhanced activation of cognate MOG-specific T cells in the central nervous system (CNS), which was dependent on FcR-, but not C1q-binding. The identification of complement-dependent and -independent pathomechanisms of MOG-Abs has implications for therapeutic strategies in MOGAD.
CRIS-Team Scopus Importer:2023-03-31
Keywords: Autoimmunity; demyelination; effector mechanisms; inflammation; neuroimmunology

Dual Fc optimization to increase the cytotoxic activity of a CD19-targeting antibody - Gehlert, Carina Lynn; Rahmati, Pegah; Boje, Ammelie Svea; Winterberg, Dorothee; Krohn, Steffen; Theocharis, Thomas; Cappuzzello, Elisa; Lux, Anja; Nimmerjahn, Falk; Ludwig, Ralf J.; Lustig, Marta; Rösner, Thies; et al. (Frontiers in Immunology, 2022)
Targeting CD19 represents a promising strategy for the therapy of B-cell malignancies. Although non-engineered CD19 antibodies are poorly effective in mediating complement-dependent cytotoxicity (CDC), antibody-dependent cell-mediated cytotoxicity (ADCC) or antibody-dependent cellular phagocytosis (ADCP), these effector functions can be enhanced by Fc-engineering. Here, we engineered a CD19 antibody with the aim to improve effector cell-mediated killing and CDC activity by exchanging selected amino acid residues in the Fc domain. Based on the clinically approved Fc-optimized antibody tafasitamab, which triggers enhanced ADCC and ADCP due to two amino acid exchanges in the Fc domain (S239D/I332E), we additionally added the E345K amino acid exchange to favor antibody hexamerization on the target cell surface resulting in improved CDC. The dual engineered CD19-DEK antibody bound CD19 and Fcγ receptors with similar characteristics as the parental CD19-DE antibody. Both antibodies were similarly efficient in mediating ADCC and ADCP but only the dual optimized antibody was able to trigger complement deposition on target cells and effective CDC. Our data provide evidence that from a technical perspective selected Fc-enhancing mutations can be combined (S239D/I332E and E345K) allowing the enhancement of ADCC, ADCP and CDC with isolated effector populations. Interestingly, under more physiological conditions when the complement system and FcR-positive effector cells are available as effector source, strong complement deposition negatively impacts FcR engagement. Both effector functions were simultaneously active only at selected antibody concentrations. Dual Fc-optimized antibodies may represent a strategy to further improve CD19-directed cancer immunotherapy. In general, our results can help in guiding optimal antibody engineering strategies to optimize antibodies’ effector functions.
CRIS-Team Scopus Importer:2022-09-30
Keywords: ADCC; ADCP; antibody hexamerization; antibody therapy; CD19; CDC; Fc engineering

Expression Profiling and Glycan Engineering of IgG Subclass 1–4 in Nicotiana benthamiana - Kallolimath, Somanath; Hackl, Thomas; Gahn, Raphaela; Grünwald-Gruber, Clemens; Zich, Wilhelm; Kogelmann, Benjamin; Lux, Anja; Nimmerjahn, Falk; Steinkellner, Herta (Frontiers in Bioengineering and Biotechnology, 2020)
IgG, the main serum immunoglobulin isotype, exists in four subclasses which selectively appear with distinctive glycosylation profiles. However, very little is known about the biological consequences mainly due to the difficulties in the generation of distinct IgG subtypes with targeted glycosylation. Here, we show a comprehensive expression and glycan modulation profiling of IgG variants in planta that are identical in their antigen binding domain but differ in their subclass appearance. While IgG1, 2, and 4 exhibit similar expression levels and purification yields, IgG3 is generated only at low levels due to the in planta degradation of the heavy chain. All IgG subtypes are produced with four distinct N-glycosylation profiles, differing in sugar residues previously shown to impact IgG activities, i.e., galactosylation, sialylation and core fucosylation. Affinity purified IgG variants are shown to be fully assembled to heterodimers but display different biochemical/physical features. All subtypes are equally well amenable to targeted glycosylation, except sialylated IgG4 which frequently accumulates substantial fractions of unusual oligo-mannosidic structures. IgG variants show significant differences in aggregate formation and endotoxin contamination which are eliminated by additional polishing steps (size exclusion chromatography, endotoxin removal treatments). Collectively we demonstrate the generation of 16 IgG variants at high purity and large glycan homogeneity which constitute an excellent toolbox to further study the biological impact of the two main Fc features, subclass and glycosylation.
CRIS-Team Scopus Importer:2020-08-28
Keywords: antibodies; glycan engineering; glycosylation; IgG subclasses; plants

Fc-engineering significantly improves the recruitment of immune effector cells by anti-ICAM-1 antibody MSH-TP15 for myeloma therapy - Klausz, Katja; Cieker, Michael; Kellner, Christian; Roesner, Thies; Otte, Anna; Krohn, Steffen; Lux, Anja; Nimmerjahn, Falk; Valerius, Thomas; Gramatzki, Martin; Peipp, Matthias (Haematologica, 2021)
Despite several therapeutic advances, patients with multiple myeloma (MM) require additional treatment options since no curative therapy exists yet. In search of a novel therapeutic antibody, we previously applied phage display with myeloma cell screening and developed TP15, a single-chain fragment variable targeting intercellular adhesion molecule 1 (ICAM-1/CD54). In order to more precisely evaluate the antibody's modes of action, fully human immunoglobulin G1 antibody variants were generated bearing the wild-type (MSH-TP15) or mutated fragment crystallizable (Fc-engineered [Fc-eng.]) region to either enhance (MSH-TP15 Fc-eng.) or prevent (MSH-TP15 Fc knockout [Fc k.o.]) Fc gamma receptor binding. Especially MSH-TP15 Fc-eng. induced significant antibody-dependent cell-mediated cytotoxicity against malignant plasma cells by recruiting natural killer cells and engaged macrophages for antibody-dependent cellular phagocytosis of tumor cells. Binding studies with truncated ICAM-1 demonstrated MSH-TP15 binding to ICAM-1 domain 1-2. Importantly, MSH-TP15 and MSH-TP15 Fc-eng. both prevented myeloma cell engraftment and significantly prolonged survival of mice in an intraperitoneal xenograft model. In the subcutaneous model MSH-TP15 Fc-eng. was superior to MSH-TP15, whereas MSH-TP15 Fc k.o. was not effective in either of the models - reflecting the importance of Fc-dependent mechanisms of action also in vivo. The efficient recruitment of immune cells and the observed anti-tumor activity of the Fc-engineered MSH-TP15 antibody hold significant potential for myeloma immunotherapy.
CRIS-Team WoS Importer:2021-08-06

FcγR dependent mechanisms of cytotoxic, agonistic, and neutralizing antibody activities. - Nimmerjahn, Falk; Gordan, Sina; Lux, Anja (Trends in immunology, 2015)
Given the widespread use of antibodies of the immunoglobulin G (IgG) class as cytotoxic, immunomodulatory, and neutralizing agents in the therapy of malignant, infectious, and autoimmune diseases, understanding the molecular and cellular mechanisms responsible for their therapeutic activity is of major importance. While Fcγ receptors (FcγR) have well-appreciated roles as effectors of cytotoxic IgG activity, it has only recently become clear that the functionality of immunomodulatory and neutralizing IgG preparations also depends on cellular FcγRs. Here, we review current models of IgG activity in infectious and inflammatory settings, and examine the importance of cell type-specific expression of FcγRs in determining functional outcome. We discuss how this knowledge may be used to improve the activity of therapeutic antibody preparations and outline important areas of focus for future research.

Fcγ receptor IIB (FcγRIIB) maintains humoral tolerance in the human immune system in vivo. - Bärenwaldt, Anne; Lux, Anja; Danzer, Heike; Spriewald, Bernd M.; Ullrich, Evelyn; Heidkamp, Gordon Frederik; Dudziak, Diana; Nimmerjahn, Falk (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Maintenance of immunological tolerance is crucial to prevent development of autoimmune disease. The production of autoantibodies is a hallmark of many autoimmune diseases and studies in mouse model systems suggest that inhibitory signaling molecules may be important checkpoints of humoral tolerance. By generating humanized mice with normal and functionally impaired Fcγ receptor IIB (FcγRIIB) variants, we show that the inhibitory Fcγ-receptor is a checkpoint of humoral tolerance in the human immune system in vivo. Impaired human FcγRIIB function resulted in the generation of higher levels of serum immunoglobulins, the production of different autoantibody specificities, and a higher proportion of human plasmablasts and plasma cells in vivo. Our results suggest that the inhibitory FcγRIIB may be an important checkpoint of humoral tolerance in the human immune system.

FcγRIIB: A modulator of cell activation and humoral tolerance - Lehmann, Birgit; Schwab, Inessa; Böhm, Sybille; Lux, Anja; Biburger, Markus; Nimmerjahn, Falk (Expert Review of Clinical Immunology, 2012)
An immune response needs to be tightly regulated to prevent excessive inflammation, which may result in the destruction of healthy tissues. At the molecular level, the strength of an immune response is determined by the integration of a multitude of positive and negative signals. This review will focus on IgG-dependent immune responses and discuss how the inhibitory receptor FcγRIIB may be involved in regulating both the afferent and efferent phases of such a response. Furthermore, we will discuss recent evidence suggesting that FcγRIIB may have important functions beyond the negative regulation of signals transduced by the B-cell receptor or activating FcγRs and could be responsible for the activity of agonistic antibodies in vivo. © 2012 Expert Reviews Ltd.
Keywords: B cell; humoral tolerance; IgG; inhibitory Fc-receptor; innate immune effector cells; IVIg

FcγRIV deletion reveals its central role for IgG2a and IgG2b activity in vivo. - Nimmerjahn, Falk; Lux, Anja; Albert, Heike; Woigk, Melissa; Lehmann, Christian; Dudziak, Diana; Smith, Patrick; Ravetch, J. V. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Cellular Fcγ receptors are essential for IgG-dependent effector functions in vivo. There is convincing evidence that selective activating Fcγ receptors are responsible for the activity of individual IgG subclasses. Thus, IgG1 activity is absent in FcγRIII-deficient mice, and several studies suggest that the activity of the most potent IgG subclasses, IgG2a and IgG2b, might be dependent on either individual or a combination of activating FcγRs. To study the role of individual activating FcγRs for IgG subclass activity, we generated an FcγRIV-deficient mouse and showed that a variety of IgG2a- and IgG2b-dependent effector functions are impaired in the absence of this activating Fc receptor in models of autoimmunity and antibody-dependent cellular cytotoxicity.

Fra1 Controls Rheumatoid Factor Autoantibody Production by Bone Marrow Plasma Cells and the Development of Autoimmune Bone Loss - Grötsch, Bettina; Lux, Anja; Rombouts, Yoann; Hoffmann, Alana; Andreev, Darja; Nimmerjahn, Falk; Xiang, Wei; Scherer, Hans Ulrich; Schett, Georg; Bozec, Aline (Journal of Bone and Mineral Research, 2019)
Next to proinflammatory cytokines, autoimmunity has been identified as a key trigger for osteoclast activation and bone loss. IgG-rheumatoid factor (IgG-RF) immune complexes, which are present in patients with rheumatoid arthritis, were shown to boost osteoclast differentiation. To date, the regulation of IgG-RF production in the absence of inflammatory triggers is unknown. Herein, we describe Fra1 as a key checkpoint that controls IgG-RF production by plasma cells and regulates autoimmune-mediated bone loss. Fra1 deficiency in B cells (Fra1ΔBcell ) led to increased IgG1-producing bone marrow plasma cells, enhanced IgG-RF production, and increased bone loss associated with elevated osteoclast numbers after immunization. The effect of IgG-RF on osteoclasts in vitro and on osteoclasts associated with bone loss in vivo was dependent on FcγR, especially FcγR3. Furthermore, immunization of WT mice with T-cell-dependent antigens induced a significant and robust decrease in Fra1 expression in bone marrow B cells, which was followed by increased IgG1 production and the induction of osteoclast-mediated bone loss. Overall, these data identify Fra1 as a key mediator of IgG-RF production and autoimmune-mediated bone loss. © 2019 American Society for Bone and Mineral Research.
EVALuna2:69394

Glycosylation of immunoglobulin G determines osteoclast differentiation and bone loss. - Harre, Ulrike; Lang, Stefanie; Pfeifle, René; Rombouts, Yoann; Frühbeißer, Sabine; Amara, Khaled; Bang, Holger; Lux, Anja; Koeleman, Carolien A.; Baum, Wolfgang; Dietel, Katharina; Gröhn, Franziska; et al. (Nature Communications, 2015)
Immunglobulin G (IgG) sialylation represents a key checkpoint that determines the engagement of pro- or anti-inflammatory Fcγ receptors (FcγR) and the direction of the immune response. Whether IgG sialylation influences osteoclast differentiation and subsequently bone architecture has not been determined yet, but may represent an important link between immune activation and bone loss. Here we demonstrate that desialylated, but not sialylated, immune complexes enhance osteoclastogenesis in vitro and in vivo. Furthermore, we find that the Fc sialylation state of random IgG and specific IgG autoantibodies determines bone architecture in patients with rheumatoid arthritis. In accordance with these findings, mice treated with the sialic acid precursor N-acetylmannosamine (ManNAc), which results in increased IgG sialylation, are less susceptible to inflammatory bone loss. Taken together, our findings provide a novel mechanism by which immune responses influence the human skeleton and an innovative treatment approach to inhibit immune-mediated bone los

How immunoglobulin G antibodies kill target cells: Revisiting an old paradigm - Biburger, Markus; Lux, Anja; Nimmerjahn, Falk (Academic Press Inc., 2014)
The capacity of immunoglobulin G (IgG) antibodies to eliminate virtually any target cell has resulted in the widespread introduction of cytotoxic antibodies into the clinic in settings of cancer therapy, autoimmunity, and transplantation, for example. More recently, it has become apparent that also the protection from viral infection via IgG antibodies may require cytotoxic effector functions, suggesting that antibody-dependent cellular cytotoxicity (ADCC) directed against malignant or virally infected cells is one of the most essential effector mechanisms triggered by IgG antibodies to protect the host. A detailed understanding of the underlying molecular and cellular pathways is critical, therefore, to make full use of this antibody effector function. Several studies over the last years have provided novel insights into the effector pathways and innate immune effector cells responsible for ADCC reactions. One of the most notable outcomes of many of these reports is that cells of the mononuclear phagocytic system rather than natural killer cells are critical for removal of IgG opsonized target cells in vivo. © 2014 Elsevier Inc.
Keywords: ADCC; ADCP; Fc-receptor; Immunoglobulin G; Natural killer cell

Human Fcγ-receptor IIb modulates pathogen-specific versus self-reactive antibody responses in lyme arthritis - Danzer, Heike; Glaesner, Joachim; Baerenwaldt, Anne; Reitinger, Carmen; Lux, Anja; Heger, Lukas; Dudziak, Diana; Harrer, Thomas; Gessner, Andre; Nimmerjahn, Falk (eLife, 2020)
Pathogen-specific antibody responses need to be tightly regulated to generate protective but limit self-reactive immune responses. While loss of humoral tolerance has been associated with microbial infections, the pathways involved in balancing protective versus autoreactive antibody responses in humans are incompletely understood. Studies in classical mouse model systems have provided evidence that balancing of immune responses through inhibitory receptors is an important quality control checkpoint. Genetic differences between inbred mouse models and the outbred human population and allelic receptor variants not present in mice; however, argue for caution when directly translating these findings to the human system. By studying Borrelia burgdorferi infection in humanized mice reconstituted with human hematopoietic stem cells from donors homozygous for a functional or a non-functional FcγRIIb allele, we show that the human inhibitory FcγRIIb is a critical checkpoint balancing protective and autoreactive immune responses, linking infection with induction of autoimmunity in the human immune system.
CRIS-Team Scopus Importer:2020-09-11
Keywords: arthritis; autoimmunity; borrelia burgdorferi; Fc-receptor; humanized mouse; immunology; inflammation; mouse

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, Jil; Lehmann, Christian; Heger, Lukas; Eissing, Nathalie; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (Science immunology, 2016)
In mice, conventional and plasmacytoid dendritic cells (DCs) derive from separate hematopoietic precursors before they migrate to peripheral tissues. Moreover, two classes of conventional DCs (cDC1 and cDC2 DCs) and one class of plasmacytoid DCs (pDCs) have been shown to be transcriptionally and functionally distinct entities. In humans, these three DC subtypes can be identified using the cell surface markers CD1c (cDC2), CD141 (cDC1), and CD303 (pDCs), albeit it remains elusive whether DC functionality is mainly determined by ontogeny or the tissue microenvironment. By phenotypic and transcriptional profiling of these three DC subtypes in different human tissues derived from a large number of human individuals, we demonstrate that DC subpopulations in organs of the lymphohematopoietic system (spleen, thymus, and blood) are strongly defined by ontogeny rather than by signals from the microenvironment. In contrast, DC subsets derived from human lung or skin differed substantially, strongly arguing that DCs react toward modulatory signals from tissue microenvironments. Collectively, the data obtained in this study may serve as a major resource to guide further studies into human DC biology during homeostasis and inflammatio
EVALuna2:6852

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, J.; Lehmann, C. H. K.; Heger, Lukas; Eissing, N.; Baranska, A.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (2017)
EVALuna2:33137

IgG1 versus IgG3: influence of antibody-specificity and allotypic variance on virus neutralization efficacy - Kallolimath, Somanath; Sun, Lin; Palt, Roman; Föderl-Höbenreich, Esther; Hermle, Antonia; Voß, Leonie; Kleim, Marina; Nimmerjahn, Falk; Gach, Johannes S.; Hitchcock, Lauren; Chen, Qiang; Melnik, Stanislav; et al. (Frontiers in Immunology, 2024)
Despite the unique advantages of IgG3 over other IgG subclasses, such as mediating enhanced effector functions and increased flexibility in antigen binding due to a long hinge region, the therapeutic potential of IgG3 remains largely unexplored. This may be attributed to difficulties in recombinant expression and the reduced plasma half-life of most IgG3 allotypes. Here, we report plant expression of two SARS-CoV-2 neutralizing monoclonal antibodies (mAbs) that exhibit high (P5C3) and low (H4) antigen binding. P5C3 and H4-IgG1 mAbs were subclass-switched to IgG3 formats, designed for efficient production and increased PK values, carrying three allotypic variations, referred to as -WT, -H, and -KVH. A total of eight mAbs were produced in glycoengineered plants that synthesize fucose-free complex N-glycans with great homogeneity. Antigen, IgG-FcγR immune complex and complement binding studies demonstrated similar activities of all mAbs. In accordance, P5C3 Abs showed minor alterations in SARS-CoV-2 neutralization (NT) and antibody-dependent cell-mediated virus inhibition (ADCVI). Clear functional differences were observed between H4 variants with superior ADCVI and NT potencies of H4 IgG3 H. Our comparative study demonstrates the production of an IgG3 variant carrying an Fc domain with equivalent or enhanced functions compared to IgG3-WT, but with the stability and PK values ​​of IgG1. Our data also demonstrate that both allotypic variability and antibody specificity are important for fine-tuning of activities, an important information for the development of future therapeutics.
CRIS-Team Scopus Importer:2024-11-22
Keywords: antibody engineering; functional activities; IgG3 allotypes; plant expression; SARS-CoV-2 antibodies

IgG Fc domains that bind C1q but not effector Fcγ receptors delineate the importance of complement-mediated effector functions. - Lee, Chang-Han; Romain, Gabrielle; Yan, Wupeng; Watanabe, Makiko; Charab, Wissam; Todorova, Biliana; Lee, Jiwon; Triplett, Kendra; Donkor, Moses; Lungu, Oana I.; Lux, Anja; Marshall, Nicholas; et al. (Nature Immunology, 2017)
Engineered crystallizable fragment (Fc) regions of antibody domains, which assume a unique and unprecedented asymmetric structure within the homodimeric Fc polypeptide, enable completely selective binding to the complement component C1q and activation of complement via the classical pathway without any concomitant engagement of the Fcγ receptor (FcγR). We used the engineered Fc domains to demonstrate in vitro and in mouse models that for therapeutic antibodies, complement-dependent cell-mediated cytotoxicity (CDCC) and complement-dependent cell-mediated phagocytosis (CDCP) by immunological effector molecules mediated the clearance of target cells with kinetics and efficacy comparable to those of the FcγR-dependent effector functions that are much better studied, while they circumvented certain adverse reactions associated with FcγR engagement. Collectively, our data highlight the importance of CDCC and CDCP in monoclonal-antibody function and provide an experimental approach for delineating the effect of complement-dependent effector-cell engagement in various therapeutic settings.

IgG sialylation occurs in B cells pre antibody secretion - Werner, Anja; Hanić, Maja; Zaitseva, Olga O.; Lauc, Gordan; Lux, Anja; Nitschke, Lars; Nimmerjahn, Falk (Frontiers in Immunology, 2024)
Sialic acids as terminal sugar residues on cell surface or secreted proteins have many functional roles. In particular, the presence or absence of α2,6-linked sialic acid residues at the immunoglobulin G (IgG) Fc fragment can switch IgG effector functions from pro- to anti-inflammatory activity. IgG glycosylation is considered to take place inside the plasma blast/plasma cell while the molecule travels through the endoplasmic reticulum and Golgi apparatus before being secreted. However, more recent studies have suggested that IgG sialylation may occur predominantly post-antibody secretion. To what extent this extracellular IgG sialylation process contributes to overall IgG sialylation remains unclear, however. By generating bone marrow chimeric mice with a B cell-specific deletion of ST6Gal1, the key enzyme required for IgG sialylation, we now show that sialylation of the IgG Fc fragment exclusively occurs within B cells pre-IgG secretion. We further demonstrate that B cells expressing ST6Gal1 have a developmental advantage over B cells lacking ST6Gal1 expression and thus dominate the plasma cell pool and the resulting serum IgG population in mouse models in which both ST6Gal1-sufficient and -deficient B cells are present.
CRIS-Team Scopus Importer:2024-06-14
Keywords: autoantibody; B cell; immunoglobulin G; sialic acid; sialylation

IgG subclass and vaccination stimulus determine changes in antigen specific antibody glycosylation in mice - Kao, Daniela; Lux, Anja; Schaffert, Anja; Lang, Roland; Altmann, Friedrich; Nimmerjahn, Falk (European Journal of Immunology, 2017)
Immunoglobulin G (IgG) glycosylation can modulate antibody effector functions. Depending on the precise composition of the sugar moiety attached to individual IgG glycovariants either pro- or anti-inflammatory effector pathways can be initiated via differential binding to type I or type II Fc-receptors. However, an in depth understanding of how individual IgG subclasses are glycosylated during the steady state and how their glycosylation pattern changes during vaccination is missing. To monitor IgG subclass glycosylation during the steady state and upon vaccination of mice with different T-cell dependent and independent antigens, tryptic digests of serum, and antigen-specific IgG preparations were analyzed by reversed phase-liquid chromatography-mass spectrometry. We show that there is a remarkable difference with respect to how individual IgG subclasses are glycosylated during the steady state. More importantly, upon T-cell dependent and independent vaccinations, individual antigen-specific IgG subclasses reacted differently with respect to changes in individual glycoforms, suggesting that the IgG subclass itself is a major determinant of restricting or allowing alterations in specific IgG glycovariants.
EVALuna2:7735

Immunoglobulin G-dependent inhibition of inflammatory bone remodeling requires pattern recognition receptor Dectin-1 - Seeling, Michaela; Pöhnl, Matthias; Kara, Sibel; Horstmann, Nathalie; Riemer, Carolina; Wöhner, Miriam; Liang, Chunguang; Brückner, Christin; Eiring, Patrick; Werner, Anja; Biburger, Markus; Altmann, Leon; et al. (Immunity, 2023)
Immunoglobulin G (IgG) antibodies are major drivers of inflammation during infectious and autoimmune diseases. In pooled serum IgG (IVIg), however, antibodies have a potent immunomodulatory and anti-inflammatory activity, but how this is mediated is unclear. We studied IgG-dependent initiation of resolution of inflammation in cytokine- and autoantibody-driven models of rheumatoid arthritis and found IVIg sialylation inhibited joint inflammation, whereas inhibition of osteoclastogenesis was sialic acid independent. Instead, IVIg-dependent inhibition of osteoclastogenesis was abrogated in mice lacking receptors Dectin-1 or FcγRIIb. Atomistic molecular dynamics simulations and super-resolution microscopy revealed that Dectin-1 promoted FcγRIIb membrane conformations that allowed productive IgG binding and enhanced interactions with mouse and human IgG subclasses. IVIg reprogrammed monocytes via FcγRIIb-dependent signaling that required Dectin-1. Our data identify a pathogen-independent function of Dectin-1 as a co-inhibitory checkpoint for IgG-dependent inhibition of mouse and human osteoclastogenesis. These findings may have implications for therapeutic targeting of autoantibody and cytokine-driven inflammation.
CRIS-Team Scopus Importer:2023-05-12
Keywords: bone; Dectin-1; Fc-receptor; glycosylation; IgG; inflammation; osteoclast; rheumatoid arthritis

Impact of differential glycosylation on IgG activity - Lux, Anja; Nimmerjahn, Falk (Advances in Experimental Medicine and Biology, 2011)
Immunoglobulin G (IgG) molecules are glycoproteins with dual functionality. While participating in the destruction of virally infected cells or healthy tissues during autoimmune disease, IgG antibodies are also used as a therapeutic agent to suppress IgG-triggered autoimmune disease and inflammation. Research of recent years has put the IgG-associated sugar moiety in the spotlight for regulating these opposing activities. This review will focus on how certain IgG glycovariants impact different IgG-dependent effector functions and how this knowledge might be used to further improve the therapeutic effectiveness of this class of molecules. © 2011 Springer Science+Businees Media, LLC.
CRIS-Team Scopus Importer:2022-09-23

Impact of immune complex size and glycosylation on IgG binding to human FcγRs. - Lux, Anja; Yu, Xiaojie; Scanlan, Chris N.; Nimmerjahn, Falk (Journal of Immunology, 2013)
IgG molecules are widely used as therapeutic agents either in the form of intact Abs or as Fc fusion proteins. Although efficient binding of the IgG Fc fragment to cellular FcγRs may be essential to achieve a high cytolytic activity, it may be advantageous for other applications to limit or abolish this interaction. Genetic or biochemical approaches have been used to generate these non-FcγR-binding IgG variants. By using soluble versions of FcγRs and monomeric versions of these altered IgG molecules, it was demonstrated that these IgG variants no longer bind to FcγRs. Importantly, however, these assays do not reflect the physiologic interaction of IgG with low-affinity cellular FcγRs occurring in the form of multimeric immune complexes. In this study, we investigated how the size of an immune complex can affect the interaction of normal and various versions of potentially non-FcγR-binding IgG variants with cellular FcγRs. We show that neither the D265A mutation nor EndoS treatment resulting in IgG molecules with only one N-acetylglucosamine and a fucose residue was fully able to abolish the interaction of all IgG subclasses with cellular FcγRs, suggesting that IgG subclass-specific strategies are essential to fully interfere with human FcγR binding.

Impact of Plasma Membrane Domains on IgG Fc Receptor Function - Kara, Sibel; Amon, Lukas; Lühr, Jennifer; Nimmerjahn, Falk; Dudziak, Diana; Lux, Anja (Frontiers in Immunology, 2020)
Lipid cell membranes not only represent the physical boundaries of cells. They also actively participate in many cellular processes. This contribution is facilitated by highly complex mixtures of different lipids and incorporation of various membrane proteins. One group of membrane-associated receptors are Fc receptors (FcRs). These cell-surface receptors are crucial for the activity of most immune cells as they bind immunoglobulins such as immunoglobulin G (IgG). Based on distinct mechanisms of IgG binding, two classes of Fc receptors are now recognized: the canonical type I FcγRs and select C-type lectin receptors newly referred to as type II FcRs. Upon IgG immune complex induced cross-linking, these receptors are known to induce a multitude of cellular effector responses in a cell-type dependent manner, including internalization, antigen processing, and presentation as well as production of cytokines. The response is also determined by specific intracellular signaling domains, allowing FcRs to either positively or negatively modulate immune cell activity. Expression of cell-type specific combinations and numbers of receptors therefore ultimately sets a threshold for induction of effector responses. Mechanistically, receptor cross-linking and localization to lipid rafts, i.e., organized membrane microdomains enriched in intracellular signaling proteins, were proposed as major determinants of initial FcR activation. Given that immune cell membranes might also vary in their lipid compositions, it is reasonable to speculate, that the cell membrane and especially lipid rafts serve as an additional regulator of FcR activity. In this article, we aim to summarize the current knowledge on the interplay of lipid rafts and IgG binding FcRs with a focus on the plasma membrane composition and receptor localization in immune cells, the proposed mechanisms underlying this localization and consequences for FcR function with respect to their immunoregulatory capacity.
CRIS-Team Scopus Importer:2020-07-24
Keywords: cell membrane; CLR; FcγR; lipid rafts; membrane; membrane localization; type I FcR; type II FcR

Inflammatory monocytes and Fcγ receptor IV on osteoclasts are critical for bone destruction during inflammatory arthritis in mice. - Seeling, Michaela; Hillenhoff, Ulrike; David, Jean Pierre; Schett, Georg; Tuckermann, Jan; Lux, Anja; Nimmerjahn, Falk (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Destruction of bone tissue by osteoclasts represents a severe pathological phenotype during inflammatory arthritis and results in joint pain and bone malformations. Previous studies have established the essential role of cytokines including TNFα and receptor-ligand interactions, such as the receptor activator of nuclear factor-kappa B-receptor activator of nuclear factor-kappa B ligand interaction for osteoclast formation during joint inflammation. Moreover, autoantibodies contribute to joint inflammation in inflammatory arthritis by triggering cellular fragment crystallizable (Fc)γ receptors (FcγR), resulting in the release of proinflammatory cytokines and chemokines essential for recruitment and activation of innate immune effector cells. In contrast, little is known about the expression pattern and function of different FcγRs during osteoclast differentiation. This would allow osteoclasts to directly interact with autoantibody immune complexes, rather than being influenced indirectly via proinflammatory cytokines released upon immune complex binding to other FcγR-expressing innate immune cells. To address this question, we studied FcγR expression and function on osteoclasts during the steady state and during acute joint inflammation in a model of inflammatory arthritis. Our results suggest that osteoclastogenesis is directly influenced by IgG autoantibody binding to select activating FcγRs on immature osteoclasts, resulting in enhanced osteoclast generation and, ultimately, bone destruction.

LILR-B1 blocks activating FcγR signaling to allow antibody dependent enhancement of dengue virus infection. - Nimmerjahn, Falk; Lux, Anja (Proceedings of the National Academy of Sciences of the United States of America, 2014)

Minimal B Cell Extrinsic IgG Glycan Modifications of Pro- and Anti-Inflammatory IgG Preparations in vivo - Schaffert, Anja; Hanic, Maja; Novokmet, Mislav; Zaytseva, Olga; Kristic, Jasminka; Lux, Anja; Nitschke, Lars; Peipp, Matthias; Pezer, Marija; Hennig, Rene; Rapp, Erdmann; Lauc, Gordan; et al. (Frontiers in Immunology, 2020)
Select residues in the biantennary sugar moiety attached to the fragment crystallizable of immunoglobulin G (IgG) antibodies can modulate IgG effector functions. Thus, afucosylated IgG glycovariants have enhanced cytotoxic activity, whereas IgG glycovariants rich in terminal sialic acid residues can trigger anti-inflammatory effects. More recent evidence suggests that terminal α2,6 linked sialic acids can be attached to antibodies post IgG secretion. These findings raise concerns for the use of therapeutic antibodies as they may change their glycosylation status in the patient and hence affect their activity. To investigate to what extent B cell extrinsic sialylation processes modify therapeutic IgG preparations in vivo, we analyzed changes in human intravenous IgG (IVIg) sialylation upon injection in mice deficient in B cells or in mice lacking the sialyltransferase 1, which catalyzes the addition of α2,6 linked sialic acid residues. By performing a time course of IgG glycan analysis with HILIC-UPLC-FLR (plus MS) and xCGE-LIF our study suggests that therapeutic IgG glycosylation is stable upon injection in vivo. Only a very small fraction of IgG molecules acquired sialic acid structures predominantly in the Fab- but not the Fc-portion upon injection in vivo, suggesting that therapeutic antibody glycosylation will remain stable upon injection in vivo.
CRIS-Team Scopus Importer:2020-02-04
Keywords: antibody; B cells; glycosylation; IgG; IVIg; sialylation

Mixed IgG Fc immune complexes exhibit blended binding profiles and refine FcR affinity estimates - Tan, Zhixin Cyrillus; Lux, Anja; Biburger, Markus; Varghese, Prabha; Lees, Stephen; Nimmerjahn, Falk; Meyer, Aaron S. (Cell Reports, 2023)
Immunoglobulin G (IgG) antibodies coordinate immune effector responses by interacting with effector cells via fragment crystallizable γ (Fcγ) receptors. The IgG Fc domain directs effector responses through subclass and glycosylation variation. Although each Fc variant has been extensively characterized in isolation, during immune responses, IgG is almost always produced in Fc mixtures. How this influences effector responses has not been examined. Here, we measure Fcγ receptor binding to mixed Fc immune complexes. Binding of these mixtures falls along a continuum between pure cases and quantitatively matches a mechanistic model, except for several low-affinity interactions mostly involving IgG2. We find that the binding model provides refined estimates of their affinities. Finally, we demonstrate that the model predicts effector cell-elicited platelet depletion in humanized mice. Contrary to previous views, IgG2 exhibits appreciable binding through avidity, though it is insufficient to induce effector responses. Overall, this work demonstrates a quantitative framework for modeling mixed IgG Fc-effector cell regulation.
CRIS-Team Scopus Importer:2023-07-28
Keywords: affinity; antibodies; avidity; CP: Immunology; effector function; Fcγ; immunology; receptors

Modulation of urelumab glycosylation separates immune stimulatory activity from organ toxicity - Reitinger, Carmen; Ipsen Escobedo, Andrea; Hornung, Chiara; Heger, Lukas; Dudziak, Diana; Lux, Anja; Nimmerjahn, Falk (Frontiers in Immunology, 2022)
Checkpoint control and immunomodulatory antibodies have become important tools for modulating tumor or self-reactive immune responses. A major issue preventing to make full use of the potential of these immunomodulatory antibodies are the severe side-effects, ranging from systemic cytokine release syndrome to organ-specific toxicities. The IgG Fc-portion has been demonstrated to contribute to both, the desired as well as the undesired antibody activities of checkpoint control and immunomodulatory antibodies via binding to cellular Fcγ-receptors (FcγR). Thus, choosing IgG subclasses, such as human IgG4, with a low ability to interact with FcγRs has been identified as a potential strategy to limit FcγR or complement pathway dependent side-effects. However, even immunomodulatory antibodies on the human IgG4 background may interact with cellular FcγRs and show dose limiting toxicities. By using a humanized mouse model allowing to study the immunomodulatory activity of human checkpoint control antibodies in vivo, we demonstrate that deglycosylation of the CD137-specific IgG4 antibody urelumab results in an amelioration of liver toxicity, while maintaining T cell stimulatory activity. In addition, our results emphasize that antibody dosing impacts the separation of side-effects of urelumab from its therapeutic activity via IgG deglycosylation. Thus, glycoengineering of human IgG4 antibodies may be a possible approach to limit collateral damage by immunomodulatory antibodies and allow for a greater therapeutic window of opportunity.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD137; Fc-receptors; glycosylation; therapeutic antibody; urelumab

Monocyte Subsets Responsible for Immunoglobulin G-Dependent Effector Functions In Vivo - Biburger, Markus; Aschermann, Susanne; Schwab, Inessa; Lux, Anja; Albert, Heike; Danzer, Heike; Woigk, Melissa; Dudziak, Diana; Nimmerjahn, Falk (Immunity, 2011)
Immunoglobulin G (IgG) antibodies confer protection against pathogenic microorganisms, serve as therapeutics in tumor therapy, and are involved in destruction of healthy tissues during autoimmune diseases. Understanding the molecular pathways and effector cell types involved in antibody-mediated effector functions is a prerequisite to modulate these activities. In this study we used two independent model systems to identify innate immune effector cells required for IgG activity in vivo. We first defined the precise repertoire of receptors for the IgG Fc fragment (FcγR) on innate immune effector cells in the blood and on tissue-resident macrophage populations. Despite expression of relevant activating FcγRs on various phagocyte populations, our data indicate that the majority of these cell types are dispensable for IgG activity in vivo. In contrast, IgG-dependent effector functions were selectively impaired in animals lacking the CX CR1 Ly6C CD11c monocyte subset, which expressed the full set of FcγRs required for IgG activity. © 2011 Elsevier Inc.

No need for constant help: human IgG2 antibodies have an autonomous agonistic activity for immunotherapy of cancer. - Lux, Anja; Nimmerjahn, Falk (Cancer cell, 2015)
Agonistic antibodies specific for members of the tumor necrosis factor receptor protein family hold great promise for immunotherapy of cancer. In this issue of Cancer Cell, White and colleagues provide evidence that the human IgG2 subclass may represent a superior backbone for the use of these antibodies in human therapy.

Of mice and men: the need for humanized mouse models to study human IgG activity in vivo. - Lux, Anja; Nimmerjahn, Falk (Journal of clinical immunology, 2013)
Antibodies of the IgG isotype have a variety of pro- and anti-inflammatory effector functions, making them attractive platforms for the development of novel therapeutic approaches. Animal model systems have been invaluable to the understanding of the underlying mechanisms of IgG activity. However, differences in the IgG subclasses and Fc receptors responsible for mediating IgG-dependent effector functions, even between such closely related species as humans and monkeys, make it difficult to predict the activity of human IgG in vivo. This review will focus on currently available animal model systems used to study human IgG activity and will propose novel model systems that might enable us to obtain a closer look at the molecular and cellular mechanisms underlying human IgG activity in vivo.

Oriented display of HIV-1 Env trimers by a novel coupling strategy enhances B cell activation and phagocytosis - Di Vincenzo, Riccardo; Beutel, Jannis; Arnold, Philipp; Wang, Yu; Damm, Dominik; Tannig, Pierre; Lux, Anja; Temchura, Vladimir; Eichler, Jutta; Überla, Klaus (Frontiers in Immunology, 2024)
Introduction: Conformationally stabilized Env trimers have been developed as antigens for the induction of neutralizing antibodies against HIV-1. However, the non-glycosylated immunodominant base of these soluble antigens may compete with the neutralizing antibody response. This has prompted attempts to couple Env trimers to organic or inorganic nanoparticles with the base facing towards the carrier. Such a site-directed coupling could not only occlude the base of the trimer, but also enhance B cell activation by repetitive display. Methods: To explore the effect of an ordered display of HIV-1 Env on microspheres on the activation of Env-specific B cells we used Bind&Bite, a novel covalent coupling approach for conformationally sensitive antigens based on heterodimeric coiled-coil peptides. By engineering a trimeric HIV-1 Env protein with a basic 21-aa peptide (Peptide K) extension at the C-terminus, we were able to covalently biotinylate the antigen in a site-directed fashion using an acidic complementary peptide (Peptide E) bearing a reactive site and a biotin molecule. This allowed us to load our antigen onto streptavidin beads in an oriented manner. Results: Microspheres coated with HIV-1 Env through our Bind&Bite system showed i) enhanced binding by conformational anti-HIV Env broadly neutralizing antibodies (bNAbs), ii) reduced binding activity by antibodies directed towards the base of Env, iii) higher Env-specific B cell activation, and iv) were taken-up more efficiently after opsonization compared to beads presenting HIV-1 Env in an undirected orientation. Discussion: In comparison to site-directed biotinylation via the Avi-tag, Bind&Bite, offers greater flexibility with regard to alternative covalent protein modifications, allowing selective modification of multiple proteins via orthogonal coiled-coil peptide pairs. Thus, the Bind&Bite coupling approach via peptide K and peptide E described in this study offers a valuable tool for nanoparticle vaccine design where surface conjugation of correctly folded antigens is required.
CRIS-Team Scopus Importer:2024-03-01
Keywords: antigen display; B cell activation; HIV-1; neutralizing antibodies; peptides; phagocytosis

Pathways Responsible for Human Autoantibody and Therapeutic Intravenous IgG Activity in Humanized Mice. - Schwab, Inessa; Lux, Anja; Nimmerjahn, Falk (Cell Reports, 2015)
Immunoglobulin G (IgG) antibodies are major drivers of autoimmune pathology, but they are also used in the form of intravenous IgG (IVIg) therapy to suppress autoantibody activity. To identify the pathways underlying human autoantibody and IVIg activity, we established a humanized mouse model of an autoantibody-dependent autoimmune disease responding to treatment with IVIg preparations. We show that the human IgG subclass strongly impacts autoantibody activity and that the Fc-receptor genotype of the human donor immune system further modulates autoantibody activity. Human mononuclear phagocytes were responsible for autoantibody activity, and IVIg therapy was able to suppress disease pathology in an Fc-fragment-dependent manner. While highly sialylated IgG glycovariants were essential for IVIg activity, it was independent of the Fc-receptor genotype and did not result in a general block of activating or the neonatal Fc-receptor. These findings may help in the development of strategies to block autoantibody and enhance therapeutic IVIg activity in humans.

Phenotyping of Macrophages in Human Immune System Mice - Voß, Leonie; Reitinger, Carmen; Lux, Anja (Methods in Molecular Biology, 2024)
Human immune system mice, also referred to as humanized mice, are a major research tool for the in vivo study of human immune system function. Upon reconstitution with human hematopoietic stem cells, all major human leukocyte populations develop in immunodeficient mice and can be detected in peripheral blood as well as in lymphatic and nonlymphatic tissue. This includes human macrophages that are intrinsically difficult to study from humans due to their organ-resident nature. In the following chapter, we provide a detailed protocol for generation of human immune system mice. We suggest that these mice are a suitable model to study human macrophage function in vivo.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Density gradient centrifugation; Flow cytometry analysis; HSC transfer; Human hematopoietic stem cell purification; Immunodeficient mice; Immunofluorescence microscopy; Magnetic cell sorting

Regulation of autoantibody activity by the IL-23-TH17 axis determines the onset of autoimmune disease. - Pfeifle, René; Rothe, Tobias; Ipseiz, Natacha; Scherer, Hans U.; Culemann, Stephan; Harre, Ulrike; Ackermann, Jochen; Seefried, Martina; Kleyer, Arnd; Uderhardt, Stefan; Haugg, Benjamin; Huebert, Axel J.; et al. (Nature Immunology, 2017)
The checkpoints and mechanisms that contribute to autoantibody-driven disease are as yet incompletely understood. Here we identified the axis of interleukin 23 (IL-23) and the TH17 subset of helper T cells as a decisive factor that controlled the intrinsic inflammatory activity of autoantibodies and triggered the clinical onset of autoimmune arthritis. By instructing B cells in an IL-22- and IL-21-dependent manner, TH17 cells regulated the expression of β-galactoside α2,6-sialyltransferase 1 in newly differentiating antibody-producing cells and determined the glycosylation profile and activity of immunoglobulin G (IgG) produced by the plasma cells that subsequently emerged. Asymptomatic humans with rheumatoid arthritis (RA)-specific autoantibodies showed identical changes in the activity and glycosylation of autoreactive IgG antibodies before shifting to the inflammatory phase of RA; thus, our results identify an IL-23-TH17 cell-dependent pathway that controls autoantibody activity and unmasks a preexisting breach in immunotoleranc

Reply to - IVIG pluripotency and the concept of Fc-sialylation: challenges to the scientist. - Schwab, Inessa; Lux, Anja; Nimmerjahn, Falk (Nature reviews. Immunology, 2014)

Suppression of Fcγ-receptor-mediated antibody effector function during persistent viral infection. - Yamada, Douglas H.; Elsaesser, Heidi; Lux, Anja; Timmerman, John M.; Morrison, Sherie L.; De La Torre, Juan Carlos; Nimmerjahn, Falk; Brooks, David G. (Immunity, 2015)
Understanding how viruses subvert host immunity and persist is essential for developing strategies to eliminate infection. T cell exhaustion during chronic viral infection is well described, but effects on antibody-mediated effector activity are unclear. Herein, we show that increased amounts of immune complexes generated in mice persistently infected with lymphocytic choriomeningitis virus (LCMV) suppressed multiple Fcγ-receptor (FcγR) functions. The high amounts of immune complexes suppressed antibody-mediated cell depletion, therapeutic antibody-killing of LCMV infected cells and human CD20-expressing tumors, as well as reduced immune complex-mediated cross-presentation to T cells. Suppression of FcγR activity was not due to inhibitory FcγRs or high concentrations of free antibody, and proper FcγR functions were restored when persistently infected mice specifically lacked immune complexes. Thus, we identify a mechanism of immunosuppression during viral persistence with implications for understanding effective antibody activity aimed at pathogen control.

Targeting B cells and autoantibodies in the therapy of autoimmune diseases. - Kao, Daniela; Lux, Anja; Schwab, Inessa; Nimmerjahn, Falk (Seminars in Immunopathology, 2014)
B cells and B cell-derived autoantibodies play a central role in the pathogenesis of many autoimmune diseases. Thus, depletion of B cells via monoclonal antibodies such as Rituximab is an obvious therapeutic intervention and has been used successfully in many instances. More recently, novel therapeutic options targeting either the autoantibody itself or resetting the threshold for B cell activation have become available and show promising immunomodulatory and anti-inflammatory effects in a variety of animal models. The aim of this review is to summarize these results and to provide an insight into the underlying molecular and cellular pathways of these novel therapeutic interventions targeting autoantibodies and B cells and to discuss their value for human therapy.

Targeting B cells in the pre-phase of systemic autoimmunity globally interferes with autoimmune pathology - Werner, Anja; Schäfer, Simon; Zaytseva, Olga; Albert, Heike; Lux, Anja; Kristic, Jasminka; Pezer, Marija; Lauc, Gordan; Winkler, Thomas; Nimmerjahn, Falk (iScience, 2021)
Systemic lupus erythematosus (SLE) is characterized by a loss of self-tolerance, systemic inflammation, and multi-organ damage. While a variety of therapeutic interventions are available, it has become clear that an early diagnosis and treatment may be key to achieve long lasting therapeutic responses and to limit irreversible organ damage. Loss of humoral tolerance including the appearance of self-reactive antibodies can be detected years before the actual onset of the clinical autoimmune disease, representing a potential early point of intervention. Notmuch is known, however, about how and to what extent this pre-phase of disease impacts the onset and development of subsequent autoimmunity. By targeting the B cell compartment in the pre-disease phase of a spontaneous mouse model of SLE we now show, that resetting the humoral immune system during the clinically unapparent phase of the disease globally alters immune homeostasis delaying the downstream development of systemic autoimmunity.
CRIS-Team WoS Importer:2021-10-15

The C5a/C5aR1 axis drives autoimmune inflammation in pemphigoid disease through the control of early Tfh cell activation, IgG autoantibody formation and IgG Fc-glycan composition - Kenno, Samyr; Gieseler-Tillmann, Jenny; Kordowski, Anna; Borus, Sina; Bieber, Katja; Ludwig, Ralf; Lux, Anja; Wuhrer, Manfred; Nimmerjahn, Falk; Koehl, Joerg (MOLECULAR IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2022-04-29

The Immunological Organ Environment Dictates the Molecular and Cellular Pathways of Cytotoxic Antibody Activity - Gordan, Sina; Albert, Heike; Danzer, Heike; Lux, Anja; Biburger, Markus; Nimmerjahn, Falk (Cell Reports, 2019)
Cytotoxic immunoglobulin G antibodies are an essential component of therapeutic approaches aimed at depleting self-reactive or malignant cells. More recent evidence suggests that the tissue in which the target cell resides influences the underlying molecular and cellular pathways responsible for cytotoxic antibody activity. By studying cytotoxic IgG activity directed against natural killer cells in primary and secondary immunological organs, we show that distinct organ-specific effector pathways are responsible for target cell depletion. While in the bone marrow, the classical complement pathway and the high-affinity Fcγ-receptor I expressed on organ-resident macrophages were both involved in removing opsonized target cells; in the spleen and blood, all activating FcγRs but not the classical complement pathway were critical for target cell killing. Our study suggests that future strategies aimed at optimizing overall cytotoxic antibody activity may need to consider organ-specific pathways to achieve a maximal therapeutic effect.
CRIS-Team Scopus Importer:2019-12-10
Keywords: antibody dependent cellular cytotoxicity; complement; cytotoxic antibody; Fc receptor; immunoglobulin G; macrophage; natural killer cell; phagocytosis

The Kaposi's sarcoma-associated herpesvirus-encoded vIRF-3 inhibits cellular IRF-5 - Wies, Effi; Hahn, Alexander; Schmidt, Katharina; Viebahn, Cornelia; Rohland, Nadine; Lux, Anja; Schellhorn, Tim; Holzer, Angela; Jung, Jae U.; Neipel, Frank (Journal of Biological Chemistry, 2009)
Kaposi's sarcoma-associated herpesvirus encodes four genes with homology to the family of interferon regulatory factors (IRFs). At least one of these viral IRFs, vIRF-3, is expressed in latently Kaposi's sarcoma-associated herpesvirus-infected primary effusion lymphoma (PEL) cells and is essential for the survival of PEL cells. We now report that vIRF-3 interacts with cellular IRF-5, thereby inhibiting binding of IRF-5 to interferon-responsive promoter elements. Consequently, vIRF-3 blocked IRF-5-mediated promoter activation. A central double helix motif present in vIRF-3 was sufficient to abrogate both DNA binding and transcriptional transactivation by IRF-5. Upon DNA damage or activation of the interferon or Toll-like receptor pathways, cytoplasmic IRF-5 has been reported to be translocated to the nucleus, which results in induction of both p53-independent apoptosis and p21-mediated cell cycle arrest. We report here that IRF-5 is present in the nuclei of PEL cells without interferon stimulation. Silencing of vIRF-3 expression in PEL cells was accompanied by increased sensitivity to interferon- mediated apoptosis and up-regulation of IRF-5 target genes. In addition, vIRF-3 antagonized IRF-5-mediated activation of the p21 promoter. The data presented here indicate that vIRF-3 contributes to immune evasion and sustained proliferation of PEL cells by releasing IRF-5 from transcription complexes. © 2009 by The American Society for Biochemistry and Molecular Biology, Inc.
CRIS-Team Scopus Importer:2022-09-23

The other side of immunoglobulin G: Suppressor of inflammation - Aschermann, Susanne; Lux, Anja; Bärenwaldt, Anne; Biburger, Markus; Nimmerjahn, Falk (Clinical and Experimental Immunology, 2010)
Summary Immunoglobulin G (IgG) molecules can have two completely opposite functions. On one hand, they induce proinflammatory responses and recruit innate immune effector cells during infection with pathogenic microorganisms or autoimmune disease. On the other hand, intravenous infusion of high doses of pooled IgG molecules from thousands of donors [intravenous IG (IVIG) therapy] represents an efficient anti-inflammatory treatment for many autoimmune diseases. Whereas our understanding of the mechanism of the proinflammatory activity of IgG is quite advanced, we are only at the very beginning to comprehend how the anti-inflammatory activity comes about and what cellular and molecular players are involved in this activity. This review will summarize our current knowledge and focus upon the two major models of either IVIG-mediated competition for IgG-triggered effector functions or IVIG-mediated adjustment of cellular activation thresholds used to explain the mechanism of the anti-inflammatory activity. © 2009 British Society for Immunology.
Keywords: Fc receptors; Glycosylation; Immunoglobulin G; Inflammation; IVIG

The pro and anti-inflammatory activities of immunoglobulin G - Lux, Anja; Aschermann, Sarah; Biburger, Markus; Nimmerjahn, Falk (Annals of the Rheumatic Diseases, 2010)
Immunoglobulin G (IgG) molecules are a family of glycoproteins essential for defending the body against invading pathogens. The antibody constant domain is very potent in initiating proinflammatory pathways such as the activation of innate immune effector cells via cellular receptors specific for the antibody constant region (Fc receptors) and the activation of the complement pathway. During autoimmune disease the normally protective antimicrobial function of these molecules is targeted to healthy tissues often with disastrous consequences. Interestingly, one successful anti-inflammatory therapy for many autoimmune diseases is the infusion of high doses of IgG molecules, the so-called intravenous IgG therapy. How one class of molecules can have such opposing functions will be the major focus of this review.

The role of Fcγ receptors in murine autoimmune thrombocytopenia - Biburger, Markus; Aschermann, Susanne; Lux, Anja; Nimmerjahn, Falk (Annals of Hematology, 2010)
Immune thrombocytopenia (ITP) can become a life-threatening condition that requires immediate medical attention. The loss in platelet numbers during ITP can be induced by a variety of triggers. Anti-platelet antibodies of several isotypes and subclasses are a major cause for ITP and are a hallmark of many complex autoimmune diseases such as systemic lupus erythematosus. Mouse models have been important to understand the effector pathways involved in antibody-mediated platelet depletion. Therapeutic interventions based on these results have been proven successful in treating human ITP, thus validating the use of these model systems. One major problem that remains to be answered is which cell populations are crucial for platelet removal. Targeting these cells directly might be a novel therapeutic strategy and will also be important to understand the underlying biological mechanisms. © 2010 Springer-Verlag.
Keywords: Autoimmunity; Fc receptors; Immunoglobulin G; Inflammation; ITP

The role of sialic acid as a modulator of the anti-inflammatory activity of IgG. - Böhm, Sybille; Schwab, Inessa; Lux, Anja; Nimmerjahn, Falk (Seminars in Immunopathology, 2012)
Immunoglobulin G (IgG) molecules can have two completely opposing activities. They can be very potent pro-inflammatory mediators on the one hand, directing the effector functions of the innate immune system towards infected cells, tumor cells or healthy tissues in the case of autoimmune diseases. On the other hand, a mixture of IgG molecules purified from the blood of ten thousands of healthy donors is used as an anti-inflammatory treatment for many autoimmune diseases since several decades. It has become evident only recently that certain residues in the sugar moiety attached to the IgG constant fragment can dramatically alter the pro- and anti-inflammatory activities of IgG. This review will focus on sialic acid residues as a modulator of the anti-inflammatory activity and provide an overview of situations where serum IgG glycosylation and sialylation is altered and which molecular and cellular pathways may be involved in this immunomodulatory pathway.

Toward Understanding How Staphylococcal Protein A Inhibits IgG-Mediated Phagocytosis - Cruz, Ana Rita; Bentlage, Arthur E.H.; Blonk, Robin; de Haas, Carla J.C.; Aerts, Piet C.; Scheepmaker, Lisette M.; Bouwmeester, Inge G.; Lux, Anja; van Strijp, Jos A.G.; Nimmerjahn, Falk; van Kessel, Kok P.M.; Vidarsson, Gestur; et al. (Journal of Immunology, 2022)
IgG molecules are crucial for the human immune response against bacterial infections. IgGs can trigger phagocytosis by innate immune cells, like neutrophils. To do so, IgGs should bind to the bacterial surface via their variable Fab regions and interact with Fcγ receptors and complement C1 via the constant Fc domain. C1 binding to IgG-labeled bacteria activates the complement cascade, which results in bacterial decoration with C3-derived molecules that are recognized by complement receptors on neutrophils. Next to FcγRs and complement receptors on the membrane, neutrophils also express the intracellular neonatal Fc receptor (FcRn). We previously reported that staphylococcal protein A (SpA), a key immune-evasion protein of Staphylococcus aureus, potently blocks IgG-mediated complement activation and killing of S. aureus by interfering with IgG hexamer formation. SpA is also known to block IgG-mediated phagocytosis in absence of complement, but the mechanism behind it remains unclear. In this study, we demonstrate that SpA blocks IgG-mediated phagocytosis and killing of S. aureus and that it inhibits the interaction of IgGs with FcγRs (FcγRIIa and FcγRIIIb, but not FcγRI) and FcRn. Furthermore, our data show that multiple SpA domains are needed to effectively block IgG1-mediated phagocytosis. This provides a rationale for the fact that SpA from S. aureus contains four to five repeats. Taken together, our study elucidates the molecular mechanism by which SpA blocks IgG-mediated phagocytosis and supports the idea that in addition to FcγRs, the intracellular FcRn is also prevented from binding IgG by SpA.
CRIS-Team Scopus Importer:2022-10-07

UNDERSTANDING HOW EPITOPE BINDING INFLUENCES ANTIBODY DEPENDENT COMPLEMENT ENGAGEMENT FOR THERAPY OF B-CELL MALIGNANCIES - Bondza, S.; Buijs, J.; Lux, Anja (JOURNAL FOR IMMUNOTHERAPY OF CANCER, 2022)
CRIS-Team WoS Importer:2022-12-23